Investigation of temperature homogeneity during infrared soldering of silicon solar cells using the finite element method - Joseph Daniel Christopher; De Rose Angela; Eberlein Dirk; Parlayan Onur; Grübel Benjamin; Beinert Andreas J.; Neuhaus Holger (EPJ Photovoltaics)
Soldering copper wires to the electrodes of solar cells is a crucial stage in the fabrication of silicon photovoltaic modules. Photovoltaic industries use infrared radiation for soldering because of its high throughput. However, this soldering process could result in an inhomogeneous temperature distribution across the solar cells. Accurately measuring the solar cell temperature during the soldering process within the stringer poses a significant challenge, hindering process optimization to reduce the inhomogeneity. In this study, a finite element model of the infrared soldering process is developed, enabling the computation of the solar cell temperature based on specified electrical power, the duration of radiation from the infrared emitters and the hotplate temperature. This model is versatile and capable of computing the temperature for different solar cell types and sizes by using their radiative and thermal properties, while also considering the shading effects of the down-holder used. The model is validated for different radiation intensities using thermocouples at different positions on the solar cells during the infrared soldering process. The maximum difference between the simulated and measured temperatures is found to be (8 ± 4) K in the peak zone. Thus, a novel and robust finite element model is developed to determine the accurate solar cell temperature during the infrared soldering process.